2013
DOI: 10.1159/000351384
|View full text |Cite
|
Sign up to set email alerts
|

Insulin in Human Milk and the Use of Hormones in Infant Formulas

Abstract: Human milk contains a substantial number of hormones and growth factors. Studies in animal models show that some of these peptides (e.g. insulin, insulin-like growth factor 1, IGF-1, epidermal growth factors) have an effect on the small intestine after orogastric administration. Recently, two efforts were made to incorporate growth factors into infant formulas. One of these efforts included the incorporation of IGF-1, and the second is an ongoing effort to evaluate the safety and efficacy of incorporating insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…However, as we did not study IR/IGF-IR double-knockout mice, we cannot exclude potential compensation during development or in very specific cellular functions. This lack of effect on growth suggests that concerns about oral insulin analogs having potential mitogenic and tumorigenic properties in the intestine are an unlikely safety concern and that the supplementation of infant formula with either IGF-I or insulin to improve gut maturation, as previously suggested (41), is also unlikely to provide major benefits.…”
Section: Discussionmentioning
confidence: 96%
“…However, as we did not study IR/IGF-IR double-knockout mice, we cannot exclude potential compensation during development or in very specific cellular functions. This lack of effect on growth suggests that concerns about oral insulin analogs having potential mitogenic and tumorigenic properties in the intestine are an unlikely safety concern and that the supplementation of infant formula with either IGF-I or insulin to improve gut maturation, as previously suggested (41), is also unlikely to provide major benefits.…”
Section: Discussionmentioning
confidence: 96%
“…Postnatal early nutrition, especially breast-feeding, is essential to infant development, protecting against obesity and metabolic dysfunction in later life 19 . Studies have shown that human milk contains high concentrations of bioactive substances such as proteins, peptides, steroids, growth factors and hormones, including insulin 20 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, insulin levels in milk appear to have a beneficial effect on gut maturation and prevent later diseases such as Crohn’s disease, celiac disease and type 1 diabetes 25 28 . Studies have documented the presence of insulin receptors in the mammalian intestine, in the jejunal and ileal brush border and intestinal crypt, in the fetal period, during the suckling period, at weaning, and in adults 20 , 29 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Once the effects of these appetite-regulating hormones of infant physiology have been established, this highlights the possibility of supplementing infant formula with appropriate concentrations of these hormones in order to improve outcomes for formula-fed infants, particularly preterm infants. Indeed, insulin has been added to formula milk in an attempt to promote better growth, as well as to accelerate intestinal maturation, 43 the ultimate aim of which is to prevent later-life diseases including allergy, autoimmune diseases and obesity. However, before these bioactive factors can be added to formula, assessment of their activities and safety in clinical trials must be undertaken.…”
Section: Discussionmentioning
confidence: 99%